2012
DOI: 10.1158/1078-0432.ccr-11-2260
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Disruptive Mutations Lead to Head and Neck Cancer Treatment Failure through Inhibition of Radiation-Induced Senescence

Abstract: Purpose Mortality of patients with head and neck squamous cell carcinoma (HNSCC) is primarily driven by tumor cell radioresistance leading to locoregional recurrence (LRR). In this study, we use a classification of TP53 mutation (disruptive vs. nondisruptive) and examine impact on clinical outcomes and radiation sensitivity. Experimental Design Seventy-four patients with HNSCC treated with surgery and postoperative radiation and 38 HNSCC cell lines were assembled; for each, TP53 was sequenced and in vitro ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
305
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(337 citation statements)
references
References 51 publications
(55 reference statements)
22
305
1
5
Order By: Relevance
“…These results were confirmed in an independent cohort of patients (45). TP53 disruptive mutations also led to treatment failure through locoregional recurrence in HNSCC (46). In contrast with these studies, we found no association of TP53 disruptive mutations with a shorter OS in advanced NSCLC.…”
Section: Discussionsupporting
confidence: 77%
“…These results were confirmed in an independent cohort of patients (45). TP53 disruptive mutations also led to treatment failure through locoregional recurrence in HNSCC (46). In contrast with these studies, we found no association of TP53 disruptive mutations with a shorter OS in advanced NSCLC.…”
Section: Discussionsupporting
confidence: 77%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19]101 Although the demonstration of resistance to oncogenemediated targeted therapy through the adaptation of cellular metabolism suggests that the rewiring of cellular metabolism plays a fundamental, convergent role for oncogenes and signal transduction in promoting tumorigenesis, little is known about how the cancer signaling networks are remodeled and which pathways are invoked to sustain survival in the presence of drugs targeting central key signaling metabolic hubs (e.g., AMPK, mTOR) that respond to an array of signaling metabolic inputs and regulate a range of downstream effector metabolic pathways. Together, our current findings suggest, for the first time, that chronic adaptation to high doses of the AMPK agonist/mTOR inhibitor metformin appears to causally involve 2 highly intertwined molecular phenomena underlying enhanced cancer aggressiveness.…”
Section: P Value Ratiomentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] While it might appear intuitive that deregulated cancer metabolism can activate pro-survival signaling and decrease druginduced apoptosis to provide a general, unspecific protection against cell injuries induced by multiple types of cytotoxicities, it is worth noting that resistance to oncogene-mediated targeted therapy has been shown to require a shift toward the very same metabolic state that is controlled by growth factor signaling. 20,21 In cancer cells sensitive to lapatinib, the small-molecule dual inhibitor of the oncogenes EGFR and HER2, receptor tyrosine kinase signaling is disrupted, and activity of its Ras, PI3K, and mTOR downstream effectors is abrogated; because oncogenedependent metabolic rewiring is prevented, cancer cell death is observed.…”
mentioning
confidence: 99%
“…Из литературных данных известно, что ТР53 мутантные раковые опухоли обладают высокой радиорезистентностью и устойчивостью к индукции апоптоза. Причины этого феномена до конца не ясны [18].…”
Section: а) б)unclassified